Impact of inclusion of post-spermatic ejaculate fraction in boar seminal doses on sperm metabolism, quality, and interaction with uterine fluid - Luongo, Chiara; Llamas-López, Pedro José; Garrappa, Gabriela; Rodríguez-Tobón, Ernesto; Grudzinska, Paulina; García Vázquez, Francisco Alberto (Springer Nature, 2025)
Boar ejaculate is composed of sperm cells and seminal plasma (SP) and is emitted in different fractions (pre-sperm fraction; spermatic-rich fraction; intermediate fraction; post-spermatic fraction), with different composition of SP and volume, which could influence the sperm quality during seminal doses preparation, conservation, and interaction with the female reproductive tract. In artificial insemination (AI) centers, seminal doses are usually prepared with the spermatic-rich and intermediate fractions, but the inclusion of other ejaculate fractions, although controversial, is beginning to be applied. The objective was to evaluate the synergic effect of accumulative ejaculated fractions on sperm functionality during seminal doses preparation, throughout storage and after incubation with uterine fluid (UF). For this purpose, a total of 57 ejaculates were collected, and the following experimental groups were prepared (n = 19 per group): (F1) spermatic-rich fraction; (F2) F1 plus intermediate fraction; (F3) F2 plus post-spermatic fraction. Each group was stored for 5 days at ∼16 °C, and the following parameters were evaluated: sperm metabolism of pure and diluted semen (day 1), sperm quality parameters (days 1, 3, 5), thermal-resistance test (TRT) and incubation with uterine fluid (UF) (day 5). Sperm metabolic rates between accumulative ejaculate fractions from pure and diluted semen did not show differences. Also, sperm quality parameters were not affected by the ejaculate fraction during storage. However, sperm subjected to TRT showed similar results except for progressive motility, which was better in F2 and F3 than F1. When sperm were incubated with UF, the quality decreased in each group, but sperm from F2 and F3 were less affected than those from F1. In conclusion, the post-spermatic fraction can be included in seminal doses for their use in AI-centers, with functionality of sperm of different SP origins not being impaired throughout the storage, and responding better to thermal and UF stress. However, further research in AI-centers is necessary to test the sperm behaviour under presented conditions.